Given that y = X^x , x>0, y>0, by taking logs, show that dy/dx = (X^x)(1+lnx)
Follow Math Help Forum on Facebook and Google+
Originally Posted by Stylis10 Given that y = X^x , x>0, y>0, by taking logs, show that dy/dx = (X^x)(1+lnx) Rewriting using logs Taking the derivative solving for y' gives sub in what y is equal to and vola!
Originally Posted by Stylis10 Given that y = X^x , x>0, y>0, by taking logs, show that dy/dx = (X^x)(1+lnx) ............. Calculate the logarithms of both sides: ............. Differentiate. Use the chainrule at the LHS and the product rule at the RHS: ............. Simplify: Substitute y by the term of the function:
View Tag Cloud